What Makes a Queer Family Queer? A Response to Cristyn Davies and Kerry H. Robinson. (March 2013) - Silin, Jonathan
In this essay I respond to Cristyn Davies and Kerry Robinson's research on queer families by remarking on the distance GLBTQI people have travelled in the last half century. I raise critical questions about the potential gains and possible losses that may result from bringing heretofore subjugated knowledges into the school curriculum. Drawing on my own biography, I also interrogate the radical edge that our outsider status once allowed us, the rapid normalization of gay life, and the foreclosure of options which that normalization has brought. Finally, I pose a distinction between non-traditional and queer families as a prompt to further investigation of how vectors of identity such as class, race, ethnicity, and religion intersect with the choices people make about constructing families and raising children.